2007
DOI: 10.1177/1541204007301292
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Mental Health Symptoms Among Delinquent and Community Youth

Abstract: Although research indicates that female offenders demonstrate higher rates of mental health symptoms than male offenders, the lack of data on directly comparable groups of delinquent and community youths has limited this comparison. The current study includes adolescents detained in juvenile detention facilities (girls = 157; boys = 276) or who resided in the community (girls = 193; boys = 242) from four different geographical locales. Results indicate that the relative magnitude of gender differences was grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
92
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 47 publications
12
92
0
3
Order By: Relevance
“…The present results are consistent with others (Abram et al, 2003;Cauffman, 2004;Cauffman, Lexcen, Goldweber, Shulman, & Grisso, 2007;Maschi, Stimmel, Morgen, Gibson, & O'Mary, 2012;Teplin et al, 2012) in showing a higher prevalence of diagnostic flags among girls than boys. One exception is that the present analysis did not find a gender difference in substance use as did Cauffman (2004) and Teplin et al (2012).…”
Section: Correlates Of Diagnostic Clusterssupporting
confidence: 96%
See 1 more Smart Citation
“…The present results are consistent with others (Abram et al, 2003;Cauffman, 2004;Cauffman, Lexcen, Goldweber, Shulman, & Grisso, 2007;Maschi, Stimmel, Morgen, Gibson, & O'Mary, 2012;Teplin et al, 2012) in showing a higher prevalence of diagnostic flags among girls than boys. One exception is that the present analysis did not find a gender difference in substance use as did Cauffman (2004) and Teplin et al (2012).…”
Section: Correlates Of Diagnostic Clusterssupporting
confidence: 96%
“…This finding points to a gender difference in not only the quantity but also the quality, and possibly the developmental trajectory, of comorbidity (Angold et al, 1999). It is not clear why justice-involved girls are more likely than justice-involved boys to receive a clinical diagnosis (for a more in-depth discussion of this issue see Cauffman et al, 2007). Whatever the case, the present results speak to the need for gender-specific intervention programming advocated by many (Hennessey et al, 2004).…”
Section: Correlates Of Diagnostic Clustersmentioning
confidence: 91%
“…The participant advocate should not be connected to the research team, but should be someone who can act in the best interest of the youths. A waiver of parental permission with accompanying inclusion of a participant advocate is an enrollment approach that has been employed successfully in multiple studies (e.g., Cauffman et al, 2007;Goldstein et al, 2011;Teplin et al, 2002;Woolard, Harvell, & Graham, 2008). Referencing the prior approval and successful use of this approach may enhance IRB review of these procedures and facilitate the approval process.…”
Section: Recruitment Obstacle: Obtaining Parental/guardian Permissionmentioning
confidence: 98%
“…Proponents of the gender-responsive approach have long highlighted the importance of these gender-specific/salient factors. Factors such as victimization and abuse, trauma, pervasive mental health concerns, family dynamics, and availability of social supports Cauffman, Lexcen, Goldweber, Shulman, & Grisso, 2007;Douglas & Plugge, 2008;Gavazzi et al, 2006;Odgers et al, 2005;Vannatta, 1996; have been suggested as important both theoretically and in numerous qualitative studies with justiceinvolved youth and adult female samples. The primary criticism of these findings has been that while the factors identified in this literature are important for general mental and social health, they have not been empirically linked to reoffending.…”
Section: Discussionmentioning
confidence: 99%